Influence of teaching activities, environmental conditions and class schedules on teacher stress measured with a smartwatch: a pilot study - Gabriela Fretes; Cèlia Llurba; Ramon Palau (OmniaScience, 2023)
To recognize and assess the job stressors that teachers face in daily practice is essential. One of the most used objective measures of stress is the heart rate (HR). This pilot study explored the use of a wearable device (smartwatch) to monitor the HR of two teachers over two weeks in the classroom. Educational context variables (subject, class size, timetable, activity learning performed) and environment variables (temperature, humidity, sun irradiance) were related with HR. The results showed significant differences on HR among the teachers according to the educational activity, time of the day, or day of the week. The environmental variables were related differently in each of the participants. The study showed the practical implications of using a smartwatch, or smart bracelet, in the field of education. It provides systematic data that be analyzed and linked to other variables, opening the possibility of measuring real-time stress in the classroom, as an alternative or complement to stress self-reports.